Mehanizem hitre tvorbe bainita pri nizkih temperaturah - Kirbiš, Peter (visokošolska dela, 2022)
A novel procedure for the obtainment of rapid bainite formation within steels was developed. Consequently the new group of steel grades exhitis very rapid bainite formation at low temperatures, commonly below 250°C. These steels develop a very fine bainitic microstructure during continuous cooling/quenching from the austenitization temperature, without the need for isothermal heat treatments. Impact toughness and other mechanical properties meanwhile remain in compliance with common standard specifications, while also retaining sufficient hardenability to ensure homogeneous properties throughout thick sections. These steels develop a hardness of up to 65HRC and a low distortion during heat treatment. This combination of mechanical properties makes such steels particularly suitable for the production of tools, rolls, knives, ballistic protection and machine parts requiring high strength.The major trait in these steels is the formation of bainite nuclei at high temperatures and the subsequent growth of bainitic ferrite at lower temperatures. Tis is in contrast with contemporary data on standardized steels where these two process are thought to occur simultaneously. The method by which this is achieved is termed Kinetically activated bainite KAB, and the group of alloys KAB steels.
Keywords: bainit v jeklih; bainite formation kinetics; bainite in steels; Disertacije; doktorske disertacije; Jeklo; kinetika tvorbe bainita; mehanizmi utrjanja; nanostructured bainite; nanostrukturni bainit; steel; strengthening mechanisms; Univerzitetna in visokošolska dela